How Brazilian and Portuguese newsrooms use information visualization in journalism: a qualitative comparative analysis - Abras, Fernanda Barros (2018)
Data journalism is understood as a flow that encompasses at least four stages of data processing – gathering, filtering, analyzing and communicating – with the latter being developed preferably in digital media in order to include interactive visualizations. This practice has been led mainly by American and British publications and only recent incorporated by newsrooms in Brazil and Portugal. This study sought to investigate the field in both countries through a literature review, interviews with stakeholders and publications’ assessment. It was verified that the Brazilian media outlets are ahead of the Portuguese, mainly because the companies in Brazil have realized the value of structuring multidisciplinary teams – comprising programmers and/or designers beyond journalists – fully dedicated to the data journalism practice. In Portugal, media outlets remain either resorting to only one data journalist – who is often absorbed by the daily hard-news – or not institutionally recognizing the data journalism practice.